Step by step arterial surgery - Choudhry, Piush (New Delhi : Jaypee-Highligts Medical Publishers, 2013)
Part of the Step by Step series, this book is a concise guide to arterial surgery for residents and fellows
Part of the Clinical Focus Series, this book provides trainees with an overview of lesions of sarcoidosis. Begins with introduction and guidance on recognising pulmonary granulomas, then depth coverage of numerous common lesions, describing their history, clinical features, differential diagnosis and treatment.
CONT 1. Vascular trauma 2.Neck 3. Upper Limb 4. Abdomen 5. Lower limb 6. Arterial Suturing
Keywords: ANÁLISIS DE GASES EN SANGRE; CIRUGÍA ARTERIAL; BLOOD GAS ANALYSIS